PELAKSANAAN MATERI BELA NEGARA DALAM MEMBENTUK KARAKTER CINTA TANAH AIR PADA MATA PELAJARAN IPS (STUDI KELAS V SDN CURAHSAWO III PROBOLINGGO) - Ludfi Arya Wardana , Shalehuddin (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2017)
This study aimed to describe the implementation of state defense content informing character of patriotism in social studies inside and outside classroom. The subject of this study was grade 5 students at SDN CURAHSAWO III PROBOLINGGO. The study was conducted from August 2016 to October 2016. Data collection used in this study were observation, interview, and documentation. Miles and Huberman’s model was used to analyze this qualitative study. Triangulation was used to validate the data. The results showed that implementation of state defense content informing character of patriotism included some stages. Teacher prepared lesson plan (RPP), syllabus, learning material, and methods in preparation stage. In implementation stage, the activities icluded were introduction, main activities, and closure that involved patriotism values.For assessing students’ outcome in afective domain, teacher used observation. The patriotism character was reflected through some students’ attitude and activities, for example keeping the classroom and school premises clean, putting the pictures of president, vice president, and national heroes inside of the classroom, demonstrating respect in flag ceremony, and speaking Indonesian language in proper manner.